The practice of relational talk in meetings / Diana Ong Mei Li - Ong, Diana Mei Li (2012)
This study explores how participants do relational work at managerial meetings to achieve their objectives. Drawing on data recorded in managerial meetings in Kuala Lumpur, this study explores how participants manoeuvre their interaction according to the norms and expectations in the workplace and at the same time achieving their objectives. Four days of formal meetings were recorded. Seven participants representing the customer side discussed their company’s issues with the appointed vendor who was represented by one member. The meetings were conducted by non-native speakers of English who frequently code-switched from Bahasa Malaysia to English in a local Malaysian setting attended by Indonesian as well as Malaysian parties. The objective of this study is to look into how relational talk, relational work and humour are displayed in the discursive behaviour of participants. To analyse relational work, Locher and Watts’ (2005) framework is applied. Based on the framework of Community of Practice by Mills (2003), relational talk and humour are conceptualised. Schiffrin’s (1994) approach to analysing data according to structure and function with Mill’s Community of Practice (2003) help to provide an in-depth data analysis. The analysis reports on how members of the six sessions of meetings use relational talk and humour to meet the acceptable norms of relational work in which the interactions occurred. The findings show that humour is generally used as building and maintaining rapport among participants. Although relational talk is seen as trivial, in this study it is a powerful and sophisticated tool in workplace meetings where members with power use it to garner support and hiding power. In order to mask their real intentions, the participants employ appropriate behaviour in their relational talk and humour.